PENGEMBANGAN MEDIA PEMBELAJARAN MENGGAMBAR BENTUK DENGAN POWERPOINT DAN AUDIO VISUAL - Aris Munandar; Abdul Aziz Ahmad; Muh Saleh Husain (Universitas Negeri Makassar, 2025)
This study adopts the 4D development model proposed by Thiagarajan (1974) to develop valid learning media using PowerPoint and audio-visual materials for teaching form drawing in Grade VII at SMPN 4 Tommo, Mamuju Regency. The research was conducted through three stages: define, design, and development. Data collection techniques included observation, validation questionnaires from material and media experts, and documentation. The collected data were analyzed using the Criterion-Referenced Assessment (PAP) approach based on Widoyoko (2009). The results indicate that: (1) the learning media achieved an average score of 4.75 from material experts in terms of content, objectives, and instructional quality, categorized as “very good,” and deemed feasible with revisions; (2) media expert evaluation on technical quality obtained an average score of 4.07, categorized as “good,” and also considered feasible with revisions. Therefore, the developed media are appropriate to support learning activities in the classroom.